The Visibility of the Disability in Terms of the Social Model: Para Shooting Sport Sample - Meltem Işik Afacan; Ersin Afacan (Journal of Educational Issues, 2024)
The body is one of the ways people express themselves. This is true not only for people without disabilities, but also for people with disabilities. Physical education and sports are one of the methods of disabled people to express themselves physically in society. The aim of this study is to contribute to increasing the visibility of disability in sports in terms of the social model. The sample of the study consists of 11 physically disabled national shooting athletes who have the right to participate in the 2021 Paralympic Games. In the study, a semi-structured interview technique was used in which theoretically, according to De Pauw, his/her thoughts on the visibility of disability in sports were used. In this study, in which qualitative research methods are used, descriptive analysis of the data is performed using both content analysis and in-depth interview. In the study, the demographic characteristics of the participants were determined. In-depth interviews were conducted with 11 people (4 women and 7 men) who voluntarily participated in the study. Findings obtained from the data after the interviews; The sub-theme of the “obstacles to participation in sports” theme is lack of materials and facilities, the sub-theme of the “attractiveness of the Paralympic Games” is the inadequate promotion of the Paralympic Games, the sub-themes of the “reaction of the social environment” are being congratulated as a positive reaction, and the shooting sport is not known as a negative reaction determined.